Development of a neural network based on pyTorch for the identification of planetary candidates among TESS mission targets - Huang, Zichen (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper Since NASA launched the Transiting Exoplanet Survey Satellite (TESS) in 2018, many exoplanets beyond the solar system have been discovered. The TESS mission has collected a magnificent amount of photometric data for scientists to analyze and its instrument observes more than 200,000 target stars in its mission. Scientists identify and analyze the patterns of light curve data for each target and determine if it is a planetary candidate or false positive due to an eclipsing binary star system or instrumental noise. We present a tool to automatically analyze the data of target stars through machine learning and a neural network built with pyTorch. When the Tess satellite finds stars that may have transits, the observation data can be downloaded through computer programs or archived. This will be a simple and time-saving tool that allows people to distinguish real transit planets from eclipsing binaries and observation equipment noise among the targets. The neural network will use the timing data of planet luminosity as input to output the probability that the galaxy really contains exoplanets. By training and testing the neural network, we find that the recall rate and accuracy rate of the network are a and B respectively. Moreover, in the case of X percent, the probability of recognition by this neural network is greater than that of non-planets.